COVID-19-Associated Multisystem Inflammatory Syndrome in a Neonate with Atypical Coronary Artery Involvement - Costa, Simonetta; Delogu, Angelica B.; Bottoni, Anthea; Purcaro, Velia; D'Andrea, Vito; Paladini, Angela; Muto, Sara; Marano, Riccardo; Savino, Giancarlo; Secinaro, Aurelio; De Benedetti, Fabrizio; Carsetti, Rita; Mortari, Eva Piano; Spanu, Teresa; Vento, Giovanni (American Journal of Perinatology, 2022)
Objective The study aimed to report a novel coronavirus disease 2019 (COVID-19)-associated multisystem inflammatory syndrome in children (MIS-C) in a neonate found to have an atypical diffuse thickening in coronary artery walls whose diagnosis required a multi-imaging approach.Study Design A neonate presented at birth with multiple organ involvement and coronary artery anomalies. A diagnosis of MIS-C associated with COVID-19 was supported by maternal severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) infection during pregnancy, and by the presence of both immunoglobulin (Ig)-G against SARS-CoV-2 and spike-specific memory B-cells response in the neonatal blood. Other plausible causes of the multiple organ involvement were excluded.Result At admission, a severe coronary artery dilatation was identified on echocardiography, supporting the diagnosis of the MIS-C Kawasaki-like disease; however, coronary artery internal diameters were found to be normal using cardiac computed tomography angiography. At discharge, comparing the two imaging techniques each other, the correct diagnosis resulted to be an abnormal thickening in coronary arterial walls. These findings suggest that the inflammatory process affecting the coronary arterial wall in MIS-C could result not only in typical coronary artery lesions such as dilatation of the lumen or aneurysms development but also in abnormal thickening of the coronary artery wall.Conclusion Our case provides an alert for pediatric cardiologists about the complexity to assess coronary artery involvement in MIS-C and raises the question that whether an abnormal vascular remodeling, with normal inner diameters, is to be considered like coronary artery dilatation for risk stratification.Key Points
Keywords: COVID-19; multisystem inflammatory syndrome in children; neonate; prenatal exposure to SARS-CoV-2; neonatal MIS-C; coronary artery involvement